2017
DOI: 10.1590/0074-02760170109
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity in cutaneous leishmaniasis

Abstract: Cutaneous leishmaniasis (CL) is a chronic disease caused by species of the protozoan Leishmania and characterised by the presence of ulcerated skin lesions. Both parasite and host factors affect the clinical presentation of the disease. The development of skin ulcers in CL is associated with an inflammatory response mediated by cells that control parasite growth but also contribute to pathogenesis. CD8+ T cells contribute to deleterious inflammatory responses in patients with CL through cytotoxic mechanisms. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Thus, the presence of DNA+histone+ structures outside the cells, our in vitro findings demonstrating CD8+ T cell produced LETs, together with T cell dominant lesions from L. braziliensis-infected individuals in the virtual absence of neutrophils (our own study, as well as a lack of transcriptome profiles consistent with neutrophils -44), led us to investigate whether T cell released LETs in cutaneous leishmaniasis lesions, and if they were related to disease progression and severity. The intensity of the inflammatory infiltrate present in lesions from patients with CL and ML is a measure of pathology severity in these diseases (24)(25)(26). As expected, our analysis of this cohort confirmed that disease progression from early to late in CL and the more severe ML form displays a more intense inflammatory infiltrate ( Supplementary Figure 2A).…”
Section: Lets Are Associated With Increased Tissue Pathology In Humansupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, the presence of DNA+histone+ structures outside the cells, our in vitro findings demonstrating CD8+ T cell produced LETs, together with T cell dominant lesions from L. braziliensis-infected individuals in the virtual absence of neutrophils (our own study, as well as a lack of transcriptome profiles consistent with neutrophils -44), led us to investigate whether T cell released LETs in cutaneous leishmaniasis lesions, and if they were related to disease progression and severity. The intensity of the inflammatory infiltrate present in lesions from patients with CL and ML is a measure of pathology severity in these diseases (24)(25)(26). As expected, our analysis of this cohort confirmed that disease progression from early to late in CL and the more severe ML form displays a more intense inflammatory infiltrate ( Supplementary Figure 2A).…”
Section: Lets Are Associated With Increased Tissue Pathology In Humansupporting
confidence: 82%
“…In addition, NETs have been associated with leishmaniasis (14,22). Thus, In order to also verify the relevance of CD8-derived LETs in a disease setting, we studies the occurrence of these structures in human tegumentary leishmaniasis (TL), given previous studies had shown that CD8+ T cell cytotoxicity was associated with tissue pathology in leishmaniasis caused by L. braziliensis infection (24)(25)(26)(27)(28). Thus, we evaluated if the progression and severity of lesions caused by L. braziliensis were associated with occurrence of CD8+ T cell derived LETs.…”
Section: Discussionmentioning
confidence: 99%
“…One probable mechanism of how cytotoxic cells mediate inflammation and tissue injury in CL is that, after degranulation of cytotoxic cells, granzyme B, and perforin are released into the extracellular space, inducing apoptosis of infected macrophages and bystander cells. In addition, extracellular granzyme B may indirectly contribute to inflammation by activating pro-inflammatory cytokines such as TNF, as well as degradation of ECM substrates, resulting in tissue injury ( 45 ). The search for correlations with clinical parameters was a strategy employed in this study in order to explore potentially relevant data in the context of CL pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the cells that initially migrate after parasite inoculation, followed by macrophages (Novais et al, 2009 ; Conceição et al, 2016 ). The production of IFN-γ by NK cells may contribute to parasite killing, or may be cytotoxic, thereby contributing to this pathology (Muniz et al, 2016 ; Campos et al, 2017 ). Subsequently, the activation of CD4 + and CD8 + T cells is observed.…”
Section: Introductionmentioning
confidence: 99%